Go for growth : - Tomasko, Robert M. (John Wiley & Sons, Inc., 1996)
Issues a bold challenge to business managers to commit their companies to sustained measurable growth and enduring success. Noted business author and management consultant Robert M. Tomasko details five distinct paths that can take any company, large or small, to higher levels of productivity and prosperity. Important points are fully illustrated with examples drawn from a wide variety of companies in a broad range of markets. Using a dynamic "people-centered" approach, he shows how to match these paths or game plans with the specific characteristics of your business and its key employees. These five paths include: Breaking the Rules: Destabilizing an industry to create new markets describes how to expand your business by violating rules or standards that are obsolete or so entrenched that no one questions them anymore, leaving the market wide open to astute individuals who can spot the telltale signs. Go for Growth tells how to identify these markets and how to seize the initiative, along the lines of Silicon Graphics and Southwest Airlines; Playing the Game: Excel by satisfying existing needs in growing markets explains the inherent strengths and weaknesses of market-driven companies that succeed by knowing and serving an existing market better than anyone else. Go for Growth tells you when and how to apply this game plan so effectively used by Marriott, PepsiCo, and Procter & Gamble; Making the Rules: Dominate the market by controlling its standards describes the strategies of the handful of companies that have managed to control, through research, market share, and product positioning, the markets in which they compete. This is the path of Disney, Intel, and Microsoft; Specializing: Thrive in niche markets details the ways companies such as Nordic Track, Rolex, and Union Carbide can seal off a portion of a market from other competitors by focusing on meeting very specific needs. Go for Growth shows the ways specialization can restore growth to companies undergoing wrenching change; Improvising: Profit from change by rolling with the punches describes the role of improvising as a growth path when no other good choices are available, and explains the numerous ways improvisers like IBM, Kodak, and many regional phone companies can capitalize on their flexibility to achieve profitability; Go for Growth drives home the point that there is no single best approach to growth for everyone by including lively, first-person accounts from managers thriving, and stumbling, in businesses following each path.